Prevalence of Recurrent Wheezing During the First Year of Life in Setúbal District, Portugal - Mallol-Villablanca, E (Elsevier Doyma, 2019)
Background: Recurrent wheezing during the first year of life is a major cause of respiratory morbidity worldwide, yet there are no studies on its prevalence in Portugal. Objective: Determine the prevalence and severity of recurrent wheezing, treatments employed and other related aspects, in infants during their first year of life in Setúbal, Portugal. Methods: This is a cross-sectional study of a random sample of infants aged 12–15 months living in Setúbal district. It uses a validated questionnaire answered by parents/caregivers at local healthcare facilities where infants attend for growth/development monitoring and/or vaccine administration. Results: Among the 202 infants surveyed, 44.6% (95% CI 37.7–51.4) had at least one episode of wheezing; and 18.3% (95% CI 12.9–23.6) had recurrent wheezing. There was significant morbidity associated to recurrent wheezing in terms of severe episodes (17.3%–95% CI 12–22.5), visits to the emergency department (26.2%–95% CI 20.1–32.2) and hospital admissions (5.4%–95% CI 2.2–8.5); 10.4% (95% CI 6.1–14.6) used inhaled corticosteroids and 7.9% (95% CI 4.1–11.6) used a leukotriene receptor antagonist. Conclusions: The prevalence of recurrent wheezing in infants during the first year of life is high and is associated with significant morbidity, presenting as a relevant public health problem. An important proportion of infants’ progress with a more severe condition, resulting in high use of health resources (visits to emergency department and hospitalisations). The prevalence of recurrent wheezing in this district of Portugal stays between those related in other European and Latin American Centres, suggesting that maybe some of the well-known risk factors are shared with affluent countries. © 2018 SEICAP